The custom of the country - Wharton, Edith, 1862-1937 (Open Road Integrated Media, 2015)
Edith Wharton's classic story of one woman's quest for wealth and status after the turn of the twentieth century Beautiful, selfish, and driven, Undine Spragg arrives in New York with all of the ambition and naiveté that her midwestern, nouveau riche upbringing afforded her. As cunning as she is lovely, Undine has but one goal in life: to ascend to the upper echelons of high society. And so with a single-minded tenacity, Undine continues to maneuver through life, finding all the while that true satisfaction remains just beyond her grasp. Hailed by Elizabeth Hardwick as?Edith Wharton's finest achievement,? The Custom of the Country is a riveting novel of ruthless ambition and a literary master class in the art of the antiheroine. This ebook has been professionally proofread to ensure accuracy and readability on all devices.